Politics of disease control in Africa and the critical role of global health diplomacy: A systematic review - Vijay Kumar Chattu; W. Andy Knight; Anil Adisesh; Sanni Yaya; K. Srikanth Reddy; Erica Di Ruggiero; Obijiofor Aginam; Garry Aslanyan; Michael Clarke; M. Rashad Massoud; Ashish Jha (Tabriz University of Medical Sciences, 2021)
Background: Africa is facing the triple burden of communicable diseases, non-communicable diseases (NCDs), and nutritional disorders. Multilateral institutions, bilateral arrangements, and philanthropies have historically privileged economic development over health concerns. That focus has resulted in weak health systems and inadequate preparedness when there are outbreaks of diseases. This review aims to understand the politics of disease control in Africa and global health diplomacy's (GHD's) critical role. Methods: A literature review was done in Medline/PubMed, Web of Science, Scopus, Embase, and Google scholar search engines. Keywords included MeSH and common terms related to the topics: "Politics," "disease control," "epidemics/ endemics," and "global health diplomacy" in the "African" context. The resources also included reports of World Health Organization, United Nations and resolutions of the World Health Assembly (WHA). Results: African countries continue to struggle in their attempts to build health systems for disease control that are robust enough to tackle the frequent epidemics that plague the continent. The politics of disease control requires the crafting of cooperative partnerships to accommodate the divergent interests of multiple actors. Recent outbreaks of COVID-19 and Ebola had a significant impact on African economies. It is extremely important to prioritize health in the African development agendas. The African Union (AU) should leverage the momentum of the rise of GHD to (i) navigate the politics of global health governance in an interconnected world(ii) develop robust preparedness and disease response strategies to tackle emerging and reemerging disease epidemics in the region (iii) address the linkages between health and broader human security issues driven by climate change-induced food, water, and other insecurities (iv) mobilize resources and capacities to train health officials in the craft of diplomacy. Conclusion: The AU, Regional Economic Communities (RECs), and African Centres for Disease Control should harmonize their plans and strategies and align them towards a common goal that integrates health in African development agendas. The AU must innovatively harness the practice and tools of GHD towards developing the necessary partnerships with relevant actors in the global health arena to achieve the health targets of the Sustainable Development Goals.